Fintech, Bank Risk-Taking, and Risk-Warning for Commercial Banks in the Era of Digital Technology - Li, Gang; Elahi, Ehsan; Zhao, Liangliang (Frontiers in Psychology, 2022)
Fintech risks commercial banks in three-way particularly operational efficiency, financial innovation, and risk management. Based on the data of 37 Chinese listed commercial banks from 2011 to 2020, the paper empirically analyzes the impact of fintech on bank risk-taking, and the intermediary effects of the three channels such as operational efficiency, financial innovation, and risk management. The results show that fintech can effectively reduce the risk of banks. The heterogeneity analysis found that the fintech strongly affects the risk-taking of state-owned banks, but not obviously for rural commercial banks. Financial efficiency, financial innovation, and risk management indirectly affect the risk-taking of banks that contributed 8.51%, 7.18%, and 5.77%, respectively. We also constructed the commercial bank risk-warning index. Based on the quarterly data of banks from 2011 to 2020, we empirically tested the early warning effect of the bank risk-warning index. The results show that when the signal month is set to 12 months, the bank risk-warning index can play a warning effect in this period.